“HOW ENGLISH BECAME GLOBAL LANGUAGE” - MamadjanovaMaftunaUktamovna; Gulomjonova Barchinoy Qobijon qizi; Abdullayeva Dilnoza Furqatjon qizi (Ta’lim innovatsiyasi va integratsiyasi, 2023)
Abstract:This article explores the historical, social, and cultural factors that contributed to the global dominance of the English language. From its humble origins as a Germanic dialect spoken by a small island community to its current status as a global lingua franca, English's ascent has been shaped by colonization, trade, technology, and cultural influence. The examination of this linguistic evolution provides insights into the complex interplay of historical events and socio-cultural dynamics that have propelled English to its current position as the world's foremost international language.